Taxonomy and Evaluations of Low-Power Listening Protocols for Machine-to-Machine Networks - Kwang-il Hwang; Sung-Hyun Yoon (Journal of Applied Mathematics)
Even though a lot of research has made significant contributions to advances in sensor networks, sensor network protocols, which have different characteristics according to the target application, might confuse machine-to-machine (M2M) network designers when they choose the protocol most suitable for their specific applications. Therefore, this paper provides a well-defined taxonomy of low-power listening protocols by examining in detail the existing low-power sensor network protocols and evaluation results. It will also be very useful for helping M2M designers understand specific features of low-power media access control protocols as they design new M2M networks.